2015
DOI: 10.1002/ceat.201500023
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Coupling of Pore Structure Evolution with Decomposition Kinetics of Limestone

Abstract: The pore structure evolution and reaction characteristics of limestone with different particle sizes during thermal decomposition were investigated experimentally. A kinetic model considering the effect of pore structure evolution was developed to simulate the multiscale coupling of the mesoscale pore structure with the macroscopic transport and microscopic chemical reaction. Over a defined particle size range, the calculated results were in good agreement with the experimental data including the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The pore structure evolution and reaction characteristics of limestone with three particle sizes during calcination at 1073 K were reported in a previous work and the results demonstrated that the influences of particle size and pore structure on the reaction mechanisms cannot be ignored . An expression is also obtained for the conversion‐time curve which displays the effects of porous structure.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…The pore structure evolution and reaction characteristics of limestone with three particle sizes during calcination at 1073 K were reported in a previous work and the results demonstrated that the influences of particle size and pore structure on the reaction mechanisms cannot be ignored . An expression is also obtained for the conversion‐time curve which displays the effects of porous structure.…”
Section: Introductionmentioning
confidence: 66%
“…In order to verify the present theoretical model and demonstrate the dynamic reaction mechanisms, the numerical solutions of the present model for the thermal decomposition rates were compared with both the experimental data and the simulated results under different chemical reaction mechanisms performed in previous literature as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these models have two notable shortcomings: they consider neither the microstructure nonuniformity nor the sintering phenomenon. Regarding the first shortcoming, Li et al modeled the calcination of limestone under N 2 atmosphere and were able to describe the evolution of porous microstructure using a bimodal pore‐size distribution. However, they did not consider the CaO sintering phenomenon, which significantly affects the overall reaction rate and microstructure when calcination is performed under atmospheres containing CO 2 .…”
Section: Introductionmentioning
confidence: 99%